2011
DOI: 10.1128/mcb.01047-10
|View full text |Cite
|
Sign up to set email alerts
|

Lineage Conversion of Murine Extraembryonic Trophoblast Stem Cells to Pluripotent Stem Cells

Abstract: In mammals, the first cell fate decision is initialized by cell polarization at the 8-to 16-cell stage of the preimplantation embryo. At this stage, outside cells adopt a trophectoderm (TE) fate, whereas the inside cell population gives rise to the inner cell mass (ICM). Prior to implantation, transcriptional interaction networks and epigenetic modifications divide the extraembryonic and embryonic fate irrevocably. Here, we report that extraembryonic trophoblast stem cell (TSC) lines are converted to induced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 57 publications
0
38
0
Order By: Relevance
“…Furthermore, overexpression of Pou5f1 in newly derived TS cells (ten passages) can drive these into the pluripotent ES (ICM-like) state (Wu et al 2011). Even well-established TS cells can be reverted to ES cells, though requiring a cocktail of pluripotency genes including Pou5f1 (Kuckenberg et al 2011). It follows that shutdown of Pou5f1 (and Nanog) activity and thereby of the pluripotency network, while not necessary for the initial specification of the TE network , is required for the TE network to achieve stability.…”
Section: Genes Involved In Trophoblast Commitmentmentioning
confidence: 99%
“…Furthermore, overexpression of Pou5f1 in newly derived TS cells (ten passages) can drive these into the pluripotent ES (ICM-like) state (Wu et al 2011). Even well-established TS cells can be reverted to ES cells, though requiring a cocktail of pluripotency genes including Pou5f1 (Kuckenberg et al 2011). It follows that shutdown of Pou5f1 (and Nanog) activity and thereby of the pluripotency network, while not necessary for the initial specification of the TE network , is required for the TE network to achieve stability.…”
Section: Genes Involved In Trophoblast Commitmentmentioning
confidence: 99%
“…Studies in embryonic stem (ES) cells showed that forced expression of Cdx2 or ablation of Oct4 induces differentiation toward a TE cell fate via CDX2-OCT4 and CDX2-Oct4 enhancer interactions [6,8]. Alternatively, in trophoblast stem (TS) cells, forced expression of Oct4 alone or in combination with other reprogramming factors promotes an ES cell fate through suppression of Cdx2 and other TS cell regulators [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, overexpression of Cdx2 in ESCs leads to TSC-like cells with highly similar morphology, developmental potential, and gene expression as embryoderived TSCs [16,22,23]. Similarly, TSCs can be converted to ESC-like iPSC by overexpressing Oct4 [24,25]. Likewise, ESCs can be converted to XEN cells using growth factors or PE transcription factors [12,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%